FGFR2 genetic variants in women with breast cancer - Dix-Peek, Thérèse; Dickens, Caroline; Augustine, Tanya N; Phakathi, Boitumelo P; Van Den Berg, Eunice J; Joffe, Maureen; Ayeni, Oluwatosin A; Cubasch, Herbert; Nietz, Sarah; Mathew, Christopher G; Hayat, Mahtaab; Neugut, Alfred I; et al. (Molecular medicine reports, 2023)
Black African populations are more genetically diverse than others, but genetic variants have been studied primarily in European populations. The present study examined the association of four single nucleotide polymorphisms (SNPs) of the fibroblast growth factor receptor 2, associated with breast cancer in non-African populations, with breast cancer in Black, southern African women. Genomic DNA was extracted from whole blood samples of 1,001 patients with breast cancer and 1,006 controls (without breast cancer), and the rs2981582, rs35054928, rs2981578, and rs11200014 polymorphisms were analyzed using allele-specific Kompetitive allele-specific PCR™, and the χ2 or Fisher's exact tests were used to compare the genotype frequencies. There was no association between those SNPs and breast cancer in the studied cohort, although an association was identified between the C/C homozygote genotype for rs2981578 and invasive lobular carcinoma. These results show that genetic biomarkers of breast cancer risk in European populations are not necessarily associated with risk in sub-Saharan African populations. African populations are more heterogenous than other populations, and the information from this population can help focus genetic risks of cancer in this understudied population.